Do-not-attempt resuscitation policy reduced in-hospital cardiac arrest rate and the cost of care in a developing country - David O. Alao; Snaha M. Abraham; Nada Mohammed; George D. Oduro; Mohammed A. Farid; Roxanne M. Roby; Chris Oppong; Arif A. Cevik (Libyan Journal of Medicine, 2024)
We aim to study the characteristics and outcomes of patients with a Do-Not-Attempt Resuscitation and to determine its impact on the Cost of In-Hospital Cardiac Arrest. A retrospective study of all adult patients admitted to the hospital from June 2021 to May 2022 who had a Do-Not-Resuscitate order. We abstracted patients’ socio-demographics, physiologic parameters, primary diagnosis, and comorbidities from the electronic medical records. We calculated the potential economic cost using the median ICU length of stay for the admitted IHCA patients during the study period. There were 28,866 acute admissions over the study period, and 788 patients had DNR orders. The median (IQR) age was 71 (55-82) years, and 50.3% were males. The most prevalent primary diagnosis was sepsis, 426 (54.3%), and cancer was the most common comorbidity. More than one comorbidities were present in 642 (80%) of the cohort. Of the DNR patients, 492 (62.4%) died, while 296 (37.6%) survived to discharge. Cancer was the primary diagnosis in 65 (22.2%) of those who survived, compared with 154 (31.3%) of those who died (P = 0.002). Over the study period, 153 patients had IHCA and underwent CPR, with an IHCA rate of 5.3 per 1,000 hospital admissions. Without a DNR policy, an additional 492 patients with cardiac arrest would have had CPR, resulting in an IHCA rate of 22.3 per 1000 hospital admissions. Most DNR patients in our setting had sepsis complicated by multiple comorbidities. The DNR policy reduced our IHCA incidence by 76% and prevented unnecessary post-resuscitation ICU care.